Nutritional and technological properties of pulp and peel flours from different mango cultivars - Izidoro, Maiqui [UNESP]; Leonel, Magali [UNESP]; Leonel, Sarita [UNESP]; Lossoli, Nathalia Aparecida Barbosa [UNESP]; Cândido, Hebert Teixeira [UNESP]; Züge, Patrícia Graosque Ulguim [UNESP]; De Jesus Assis, Jaciene Lopes (FapUNIFESP (SciELO), 2023)
Global mango production generates significant agricultural and industrial waste, including non-standard fruits and peels. Herein, flours obtained from the immature fruits of four mango cultivars (Haden, Keitt, Parwin, and Tommy Atkins) were characterized for their physicochemical properties with the goal of valorization as an ingredient in functional food products. Regardless of cultivar, the peel flours represented excellent sources of fiber, with notable calcium, magnesium, manganese, carotenoids, and antioxidant contents as well as high percentage of large particles and good water retention capacity. Pulp flours exhibit high starch content, light color, and fine granulometry. The mango cultivars strongly interfered with the differentiation of the mango peel and pulp flours. The results presented herein show that understanding the characteristics of flours obtained by processing different parts of the fruits of various cultivars can produce composite mango flours with different nutritional and technological properties, expanding their possible uses in food products and driving sustainable agricultural production in terms of efficient crop waste management.
Keywords: carotenoids; microstructure; minerals; proximate composition; technological properties